Congestive Heart Failure and Cardiac Transplantation : Clinical, Pathology, Imaging and Molecular Profiles - Garry, Daniel J.; Wilson, Robert F.; Vlodaver, Zeev (Springer International Publishing : Imprint: Springer, 2017)
This book is a comprehensive overview of heart failure and cardiac transplantation and integrates scientific and clinical information about the physiology, pathophysiology, diagnosis, and treatment of this disorder. Organized into five parts, it reviews the history and basic mechanisms of heart failure; etiology of heart failure; heart failure disease progression; advanced therapies for heart failure; and cardiac transplantation. The book presents basic concepts in the physiology, molecular biology, pathology, and epidemiology of the normal and failing heart; known causes of heart failure, such as right heart failure, valvular cardiomyopathy, molecular mechanisms of sarcomeric cardiomyopathies, and neuromuscular cardiomyopathy; cardiorenal syndrome; neurohormonal activation; cardiac resynchronization, ventricular assist devices; regenerative mechanisms; orthotopic heart transplantation; early and late management of the post-transplant patient; heart transplantation and antibody-mediated rejections; heart-lung transplantation; and cardiac xenotransplantation. Featuring contributions from leaders in the fields of heart failure, cardiac transplantation, cardiac pathology, and cardiovascular molecular research, Congestive Heart Failure and Cardiac Transplantation is a valuable compendium for cardiologists, cardiothoracic surgeons, researchers, trainees, and students. .
Keywords: Medicine.; Cardiology.; Cardiac surgery.; Thoracic surgery.; Surgical transplantation.; elektronické knihy; electronic books